Comparative Evaluation of Topical Betamethasone Dipropionate Lotion 0.05% versus its Combination with Intralesional Triamcinolone Acetonide Injection in Alopecia Areata: A Randomised Controlled Trial - Amit kumar tiwari; Pooja Ameta; Pradeep garg; Naushin aara (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Alopecia Areata (AA) is non-cicatricial patchy hair loss, which is fairly common and may evoke feelings of vulnerability and loss of self-esteem in patients. Many different treatment modalities have been recommended, including topical, systemic, and intralesional corticosteroids (ILCs). However, no treatment has consistently produced satisfactory results, and various topical therapies used in the past have shown limited effectiveness. ILC is the most commonly used treatment for AA, especially in patients with <50% area involved. Despite this, there is a lack of adequately powered randomised controlled trials assessing the efficacy, safety, and duration of response. Aim: To compare the efficacy of intralesional triamcinolone acetonide injection, topical betamethasone dipropionate lotion 0.05%, and their combination in treating AA. Materials and Methods: This randomised controlled trial was conducted at the Department of Dermatology, SMS Medical College, a Tertiary Care Hospital in Jaipur, Rajasthan, India, over a one-year period from August 2012 to July 2013. The study included patients aged 11 to 50 years who were willing to provide informed consent. A total of 120 patients were randomised into two groups (Group A and Group B) of 60 patients each. Twenty patients did not follow up, leaving 53 patients in Group A and 47 patients in Group B who completed the study were 53 in group A and 47 in group B. Group A received topical betamethasone dipropionate lotion 0.05% with single-night application and intralesional triamcinolone acetonide 10 mg/mL at baseline, 4, 8, and 12 weeks. Group B received topical betamethasone dipropionate lotion 0.05% with single-night application and intralesional normal saline at the same intervals. Patients were followed up for an additional 12 weeks. Responses were evaluated using the Hair Regrowth Grade (HRG) scale, and statistical analysis was performed using the Chi-square test. Results: Among the study population, the majority of patients (49, 41%) were in the age group of 21-30 years, with 91 males and 29 females. At the end of the 12-week treatment and 12- week follow-up period, Group A showed greater improvement, with 62% of patients achieving hair regrowth grade scale S-IV (76-100%), and 87% {S-IV (76-100%)} respectively, as compared to only 13% in Group B. Similarly, in the follow-up period, Group A had a higher percentage of patients with S-IV (76-100%) regrowth (87%) compared to Group B (32%). Conclusion: This study concludes that intralesional triamcinolone acetonide 10 mg/mL is an effective and safe treatment option for AA. The addition of single-night application of betamethasone dipropionate 0.05% lotion yields better results than using either treatment alone.